An accurate retrieval of leaf water content from mid to thermal infrared spectra using continuous wavelet analysis - Ullah, Saleem; Skidmore, Andrew K.; Naeem, Mohammad; Schlerf, Martin (The Science of the total environment, 2012)
Leaf water content determines plant health, vitality, photosynthetic efficiency and is an important indicator of drought assessment. The retrieval of leaf water content from the visible to shortwave infrared spectra is well known. Here for the first time, we estimated leaf water content from the mid to thermal infrared (2.5–14.0μm) spectra, based on continuous wavelet analysis. The dataset comprised 394 spectra from nine plant species, with different water contents achieved through progressive drying. To identify the spectral feature most sensitive to the variations in leaf water content, first the Directional Hemispherical Reflectance (DHR) spectra were transformed into a wavelet power scalogram, and then linear relations were established between the wavelet power scalogram and leaf water content. The six individual wavelet features identified in the mid infrared yielded high correlations with leaf water content (R2=0.86 maximum, 0.83 minimum), as well as low RMSE (minimum 8.56%, maximum 9.27%). The combination of four wavelet features produced the most accurate model (R2=0.88, RMSE=8.00%). The models were consistent in terms of accuracy estimation for both calibration and validation datasets, indicating that leaf water content can be accurately retrieved from the mid to thermal infrared domain of the electromagnetic radiation. ► The mid and thermal infrared spectra are sensitive to variation in leaf water content. ► Continuous wavelet analysis detected the variation caused by leaf water content. ► The selected wavelet features are highly correlated with leaf water content. ► Mid wave and thermal infrared spectra have the potential to estimate leaf water content.